Framing Pemberitaan Maraknya Kekerasan Seksual Terhadap Remaja Putri di Media Sosial - Dina Lorensa; Gina Elisa (CV. Ulil Albab Corp, 2024)
In today's digital age, numerous mass media platforms have transitioned into online formats, such as news websites, portals, and cyber media. This shift has not only altered the way the public consumes news, but also made accessing information online much more convenient compared to traditional print media. Unlike other forms of media, online platforms offer distinct advantages, including the absence of geographical restrictions, facilitating easier access to information for individuals both domestically and internationally. One prevalent issue on social media platforms is cyber sexual harassment, which has garnered increasing attention due to its escalating prevalence in cyberspace. Goldberg has noted a surge in internet users engaging in cyber sexual harassment activities on social media in recent years. The term